2019
DOI: 10.1021/acs.biochem.9b00822
|View full text |Cite
|
Sign up to set email alerts
|

Protein Footprinting and X-ray Crystallography Reveal the Interaction of PD-L1 and a Macrocyclic Peptide

Abstract: Blocking interactions between PD-1 and PD-L1 opens a new era of cancer treatment involving immunity modulation. Although most immunotherapies use monoclonal antibodies, smallmolecule inhibitors offer advantages. To facilitate development of small-molecule therapeutics, we implemented a rapid approach to characterize the binding interfaces of small molecule inhibitors with PD-L1. We determined its interaction with a synthetic macrocyclic peptide by using two mass-spectrometry-based approaches, hydrogen-deuteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 77 publications
(140 reference statements)
0
29
0
Order By: Relevance
“…Both general labeling strategies and amino acid specific methods have proven useful in the study of proteins. Combination of footprinting strategies or other MS‐based structural techniques such as ion mobility, top‐down proteomics, and X‐ray crystallography (Niu et al, 2020) have demonstrated the complementary nature of protein footprinting. Michael Gross has been at the forefront of innovation in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Both general labeling strategies and amino acid specific methods have proven useful in the study of proteins. Combination of footprinting strategies or other MS‐based structural techniques such as ion mobility, top‐down proteomics, and X‐ray crystallography (Niu et al, 2020) have demonstrated the complementary nature of protein footprinting. Michael Gross has been at the forefront of innovation in the field.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the data, raw data files were subjected to Byos (Protein Metrics) for database searching against the amino acid sequences of the corresponding proteins and reversed decoys of all possible peptides (Bern et al, 2012;Niu et al, 2020). The modification of acetylation (+42.010565) was added as variable modifications targeting protein N-termini, Lys, Ser, Thr, and Tyr residues for searching of Sulfo-NHS-Acetate modified samples (Brier et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported the crystal structures of PD-1 7 and PD-L1 8 . These data have determined that the interacting domains of these proteins lack cavities to host low-molecular-weight compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These data have determined that the interacting domains of these proteins lack cavities to host low-molecular-weight compounds. Consequently, the many attempts to develop pharmochemical inhibitors of PD-1 and PD-L1 have not been successful enough 8,9 . In contrast, monoclonal antibodies effectively block the immunosuppressive actions that are triggered by PD-1 and PD-L1.…”
Section: Introductionmentioning
confidence: 99%